(untitled) (Journal of the Bangladesh Agricultural University, 2016)
Field trials were conducted using ten rice genotypes including four national and international check varieties under drought prone rainfed environments of Rangpur, Nilphamari, Kurigram and Lalmonirhat districts of Bangladesh in Transplant Aman 2012 season to evaluate the growth duration and grain yield stability as well as adaptability. The experiment used randomized complete block design with three replications. Growth duration and Grain yield data were subjected to Additive Main effects and Multiplicative Interaction (AMMI) analysis. The mean growth duration of 10 genotypes over four environments showed that the longest growth duration was found for IR83383-B-B-129-4 (115.6 days) and the lowest growth duration was found for BRRI dhan56 (Ck) (113.4 days). IR82635-B-B-145-1 produced maximum 4.28 t/ha grain yield followed by 4.28 t/ha in IR82589-B-B-84-3 and the lowest grain yield was recorded for IR83376-B-B-130-2 with 3.24 t/ha. It was evident from the AMMI 1 biplot analysis that IR83377-B-B-93- 3, IR83383-B-B-129-4, IR82635-B-B-145-1, IR82635-B-B-75-2 and BRRI dhan56 (Ck) generally exhibited high yield with high main (additive) effects showing positive first principal component of the interaction (IPCA1), but IR82635-B-B-145-1 being the overall best. Hence, IR82635-B-B-145-1 was identified as specially adapted to Lalmonirhat and this environment was considered as the wide range suitable environment for the genotype. Lalmonirhat could be regarded as a good selection site for rice improvement due to stable yields. IR83377-B-B-93-3, IR82635-B-B-145-1, IR83383-B-B-129-4, IRRI 123 (Ck), BRRI dhan57 (Ck) and BINA dhan7 (Ck) were hardly affected by the G × E interaction and would perform well across a wide range of environments. In AMMI 2 biplot, IR82635-B-B-145-1 and IRRI 123 (Ck) was more responsive since they were away from the origin whereas other genotypes were nearer to the origin and hence they were more stable to different environments. IR83383-B-B-129-4 was very close to the origin, so it was more stable to different environments. Similarly Rangpur Sadar and Lalmonirhat showed similar potentiality over IR83383-B-B-129-4. The study it revealed that IR83377-B-B-93-3, IR83383-B-B-129-4, IR82635-B-B-145-1, IR82635-B-B-75-2 and IR82589-B-B-84-3 has the potentiality to show drought tolerance for the regions and might be suitable for releasing as a variety after conducting proper yield evaluation trials and Distinction, Uniformity and Stability (DUS) tests. J. Bangladesh Agril. Univ. 14(1): 23-30, June 2016